1983
DOI: 10.1038/clpt.1983.86
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose ceftriaxone kinetics in functionally anephric patients

Abstract: The disposition profile of ceftriaxone was studied in 12 functionally anephric patients (creatinine clearance less than 10 ml/min) who received bolus injections of 150, 500, and 1500 mg IV in a noncrossover fashion. As in healthy subjects, the kinetics in uremic patients were nonlinear for total (bound plus unbound) and linear for free (unbound) drug. The plasma protein binding was reduced due to a decreased association constant, resulting in a doubling of the free fraction in plasma. Ten of 12 patients showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

1984
1984
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
3
12
1
Order By: Relevance
“…The broken lines represent the average concentration-time profiles of ceftriaxone in plasma after intravenous infusion of a 1-g dose for healthy young (---; n = 8) and elderly (--; n = 8) subjects with normal renal function. those of Cohen et al (3) and Stoeckel et al (14). These investigators concluded from their data that no changes in the dosage regimen of ceftriaxone would be required for endstage renal disease patients with normal hepatic function.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The broken lines represent the average concentration-time profiles of ceftriaxone in plasma after intravenous infusion of a 1-g dose for healthy young (---; n = 8) and elderly (--; n = 8) subjects with normal renal function. those of Cohen et al (3) and Stoeckel et al (14). These investigators concluded from their data that no changes in the dosage regimen of ceftriaxone would be required for endstage renal disease patients with normal hepatic function.…”
Section: Discussionsupporting
confidence: 50%
“…A substantially prolonged half-life of ceftriaxone in a small percentage of dialysis patients was also observed by may be due to an impaired biliary excretion process, which is the alternate pathway of elimination for ceftriaxone in humans (12)(13)(14). It is suggested, therefore, that ceftriaxone concentrations in plasma should be monitored in the patients with end-stage renal disease to determine whether dosage adjustments are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced CLNRS with declining renal function have been reported for 1-lactam antibiotics such as cefsulodin (8), carumonam (11), cefixime (9), and ceftriaxone (16). The mechanism(s) responsible for this decline in CLNR has not been elucidated for f-lactam antibiotics that are primarily eliminated unchanged.…”
Section: Resultsmentioning
confidence: 96%